Pathology of macrophage activation syndrome in humanized NSGS mice. (January 2021) - Tarrant, James C.; Binder, Zev A.; Bugatti, Mattia; Vermi, William; van den Oord, Joost; Ranieri, Brona; Assenmacher, Charles-Antoine; Hoepp, Natalie; O'Rourke, Donald M.; Shan, Xiaochuan; Danet-Desnoyers, Gwenn; Radaelli, Enrico
Abstract: "Humanized" immunodeficient mice generated via the transplantation of CD34+ human hematopoietic stem cells (hHSC) are an important preclinical model system. The triple transgenic NOD.Cg- Prkdc scid Il2rg tm1Wjl Tg(CMV-IL3, CSF2, KITLG)1Eav/MloySzJ (NSGS) mouse line is increasingly used as recipient for CD34+ hHSC engraftment. NSGS mice combine the features of the highly immunodeficient NSG mice with transgenic expression of the human myeloid stimulatory cytokines GM-CSF, IL-3, and Kit ligand. While generating humanized NSGS (huNSGS) mice from two independent cohorts, we encountered a fatal macrophage activation syndrome (MAS)-like phenotype resulting from the transplantation of CD34+ hHSC. huNSGS mice exhibiting this phenotype declined clinically starting at approximately 10 weeks following CD34+ hHSC engraftment, with all mice requiring euthanasia by 16 weeks. Gross changes comprised small, irregular liver, splenomegaly, cardiomegaly, and generalized pallor. Hematological abnormalities included severe thrombocytopenia and anemia. Pathologically, huNSGS spontaneously developed a disseminated histiocytosis with infiltrates of activated macrophages and hemophagocytosis predominantly affecting the liver, spleen, bone marrow, and pancreas. The infiltrates were chimeric with a mixture of human and mouse macrophages. Immunohistochemistry suggested activation of the inflammasome in both human and murine macrophages. Active Epstein-Barr virus infection was not a feature. Although the affected mice exhibited robust chimerism of the spleen and bone marrow, the phenotype often developed in the face of low chimerism of the peripheral blood. Given the high penetrance and early lethality associated with the MAS-like phenotype here described, we urge caution when considering the use of huNSGS mice for the development of long-term studies. Highlights: NSGS mice engrafted with CD34+ hHSC (huNSGS) develop a macrophage activation syndrome-like phenotype. Macrophagic inflammation in huNSGS mice contains both human and murine components. Active EBV infection is not a feature. The macrophage activation syndrome-like phenotype can develop in the face of low chimerism of the peripheral blood.